Recent progress in 2D/quasi-2D layered metal halide perovskites for solar cells. Issue 24 (4th June 2018) - Yan, Jielin; Qiu, Weiming; Wu, Gang; Heremans, Paul; Chen, Hongzheng
Abstract : This review summarized the recent progress in 2D/quasi-2D layered metal halide perovskites for solar cells. Abstract : As an important category of perovskite materials, two-dimensional (2D) perovskites are attracting increasing research attention these days. Their possibility of combining high performance and stability for perovskite based optoelectronic devices has triggered a new wave of research. This review mainly focuses on the application of 2D perovskite materials for solar cells. We start with a brief introduction of 2D perovskite structures and their unique properties. The recent progress in 2D perovskite solar cells is summarized in three aspects according to the existing forms of the perovskite materials in the devices. In the end, a short outlook with our opinion is given to indicate the possible development trend for this kind of perovskite material.